Odds against tomorrow [a novel] - Rich, Nathaniel 1980- (Farrar, Straus and Giroux, 2013)
While working for a mysterious financial consulting firm that offers insurance to corporations against impending catastrophic events, a gifted young mathematician becomes increasingly obsessed with doomsday scenarios until one of his actual worst-case scenarios unfolds in Manhattan
Keywords: Scientists / Fiction; Fiktionale Darstellung